Experimental Study on a Compound Parabolic Concentrator Tubular Solar Still Tied with Pyramid Solar Still - T. Arunkumar; K. Vinothkumar; Amimul Ahsan; R. Jayaprakash; Sanjay Kumar (IntechOpen, 2012)
None